Carbon Stock Assessments On Imperata And Shrub Lands In Paninggahan Village - Primanika, Aries - (STKIP PGRI Sumbar, 2014)
The issue of climate change and global warming has become an important issue in various parts of the world. This problem has become main agenda of the United Nations (UN). The major contribution global warming are Carbon Dioxide (CO2) and Methane (CH4) resulting from the burning of fossil fuels, fire land and agricultural activities. This research aimed at determining carbon stocks on imperata and shrub land in Nagari Paninggahan. This research using quantitative descriptive method. Samples taken on the basis of imperata and shrub land.Collecting data done with two stages, the first one was done collecting data in the field and the second is the calculation and data analysis. This research result indicates that the tot highest carbon stock is found in shrub land reached 38.4 tons C / ha. The lowest carbon stock is in the imperata land with 4.3 tons C / ha. The average of carbon stock in shrub land reached 26.3 ton C/ha while in imperata land as 26.3 ton C/ha. The imperata and shrub land have a potential in carbon stock with a better tree management.